<u>Given</u>:
The given expression is ![18^{x^{2}+4 x+4}=18^{9 x+18}](https://tex.z-dn.net/?f=18%5E%7Bx%5E%7B2%7D%2B4%20x%2B4%7D%3D18%5E%7B9%20x%2B18%7D)
We need to determine the solution of the given expression.
<u>Solution</u>:
Let us solve the exponential equations with common base.
Applying the rule, if
then ![f(x)=g(x)](https://tex.z-dn.net/?f=f%28x%29%3Dg%28x%29)
Thus, we have;
![x^{2}+4 x+4=9 x+18](https://tex.z-dn.net/?f=x%5E%7B2%7D%2B4%20x%2B4%3D9%20x%2B18)
Subtracting both sides of the equation by 9x, we get;
![x^{2}-5 x+4=18](https://tex.z-dn.net/?f=x%5E%7B2%7D-5%20x%2B4%3D18)
Subtracting both sides of the equation by 18, we have;
![x^{2}-5 x-14=0](https://tex.z-dn.net/?f=x%5E%7B2%7D-5%20x-14%3D0)
Factoring the equation, we get;
![x^2-7x+2x-14=0](https://tex.z-dn.net/?f=x%5E2-7x%2B2x-14%3D0)
Grouping the terms, we have;
![(x^2-7x)+(2x-14)=0](https://tex.z-dn.net/?f=%28x%5E2-7x%29%2B%282x-14%29%3D0)
Taking out the common term from both the groups, we get;
![x(x-7)+2(x-7)=0](https://tex.z-dn.net/?f=x%28x-7%29%2B2%28x-7%29%3D0)
Factoring out the common term (x - 7), we get;
![(x+2)(x-7)=0](https://tex.z-dn.net/?f=%28x%2B2%29%28x-7%29%3D0)
![x+2=0 \ and \ x-7=0](https://tex.z-dn.net/?f=x%2B2%3D0%20%5C%20and%20%5C%20x-7%3D0)
![x=-2 \ and \ x=7](https://tex.z-dn.net/?f=x%3D-2%20%5C%20and%20%5C%20x%3D7)
Thus, the solution of the exponential equations is x = -2 and x = 7.
Hence, Option C is the correct answer.